Exploring the feasibility and validity of a pragmatic approach to estimating the impact of long-term care: The 'expected' ASCOT method. (2019) - Malley, Juliette; Rand, Stacey; Netten, Ann; Towers, Ann-Marie; Forder, Julien
No abstract available